The World Bank as a Political, Intellectual, and Financial Actor: It's First Half Century - Mendes Pereira, Joao Marcio [UNESP] (Univ Nacl La Plata, Fac Law & Science, 2017)
This article analyzes the history of the World Bank during its first fifty years. It is argued that since its beginnings the Bank has used credit as a lever to expand its influence and institutionalize economic ideas, concepts of the world, and political prescriptions in client states. Behind its technical facade, the Bank has always acted, albeit in different forms, in the interface of the political, economic, and intellectual fields at the international level, due to its singular condition as a lender, political actor, and inductor of ideas and prescriptions about what to do in questions of capitalist development, from an Anglo-Saxon perspective. Based on a wide and varied international literature and the sources of the institution itself, the text approaches the theme taking into account the US policy towards the institution, changes in international economic policy, and the principal decisions of the Bank's board.
Keywords: World Bank; US foreign policy; economic liberalism; multilateralism; international development aid